Fractional Reyes-Style Adaptive Tessellation for Continuous Level of Detail - Liktor, G.; Pan, M.; Dachsbacher, C. (Computer graphics forum, 2014)
In this paper we present a fractional parametric splitting scheme for Reyes‐style adaptive tessellation. Our parallel algorithm generates crack‐free tessellation from a parametric surface, which is also free of sudden temporal changes under animation. Continuous level of detail is not addressed by existing Reyes‐style methods, since these aim to produce subpixel‐sized micropolygons, where topology changes are no longer noticeable. Using our method, rendering pipelines that use larger triangles, thus sensitive to geometric popping, may also benefit from the quality of the split‐dice tessellation stages of Reyes. We demonstrate results on a real‐time GPU implementation, going beyond the limited quality and resolution of the hardware tessellation unit. In contrast to previous split‐dice methods, our split stage is compatible with the fractional hardware tessellation scheme that has been designed for continuous level of detail.